Dampak Work Demands terhadap Turnover Intention melalui Burnout dan Work-Family Conflict - Angellica Berliana Dewi; Nina Nurhasanah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study examines the impact of Work Demands (WD) on Turnover Intention (TI), considering the mediation of Burnout (BO) and Work-Family Conflict (WFC) among employees in the private banking sector residing in the Jakarta area. This research is motivated by the high Turnover Intention among Generation Z employees due to work pressure and role imbalance. This study aims to analyse the effect of WD on TI and to examine the mediating roles of BO and WFC in that relationship. This quantitative research involved 240 respondents selected thru purposive sampling and analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). The results show that WD has a positive and significant effect on BO (β=0.501) and WFC (β=0.392). BO has a positive and significant effect on TI (β=0.698), while WFC does not have a significant effect on TI (β=0.103). Indirectly, WD has a significant effect on TI thru BO (β=0.350), but not thru WFC (β=0.040). The implications of this research emphasize the need for a more realistic evaluation of workload and work targets, adjustment of the number of clients or daily targets for front liners, provision of counselling services and employee assistance programs (EAP), stress management training, as well as monitoring burnout thru periodic internal surveys to reduce turnover intention and achieve a more balanced work schedule.